MoChlo: A Versatile, Modular Cloning Toolbox for Chloroplast Biotechnology. Issue 3 (24th January 2019) - Occhialini, Alessandro; Piatek, Agnieszka A.; Pfotenhauer, Alexander C.; Frazier, Taylor P.; Stewart, C. Neal; Lenaghan, Scott C.
Abstract : The MoChlo kit is a modular tool for rapid assembly of chloroplast transformation vectors, designed to accelerate metabolic engineering in plastids. Abstract: Plant synthetic biology is a rapidly evolving field with new tools constantly emerging to drive innovation. Of particular interest is the application of synthetic biology to chloroplast biotechnology to generate plants capable of producing new metabolites, vaccines, biofuels, and high-value chemicals. Progress made in the assembly of large DNA molecules, composing multiple transcriptional units, has significantly aided in the ability to rapidly construct novel vectors for genetic engineering. In particular, Golden Gate assembly has provided a facile molecular tool for standardized assembly of synthetic genetic elements into larger DNA constructs. In this work, a complete modular chloroplast cloning system, MoChlo, was developed and validated for fast and flexible chloroplast engineering in plants. A library of 128 standardized chloroplast-specific parts (47 promoters, 38 5ʹ untranslated regions [5ʹUTRs], nine promoter:5ʹUTR fusions, 10 3ʹUTRs, 14 genes of interest, and 10 chloroplast-specific destination vectors) were mined from the literature and modified for use in MoChlo assembly, along with chloroplast-specific destination vectors. The strategy was validated by assembling synthetic operons of various sizes and determining the efficiency of assembly. This method was successfully used to generate chloroplast transformation vectors containing up to seven transcriptional units in a single vector (∼10.6-kb synthetic operon). To enable researchers with limited resources to engage in chloroplast biotechnology, and to accelerate progress in the field, the entire kit, as described, is available through Addgene at minimal cost. Thus, the MoChlo kit represents a valuable tool for fast and flexible design of heterologous metabolic pathways for plastid metabolic engineering.